Cytomorphological spectrum of hand, wrist, and foot lesions at tertiary care center in central India. Issue 11 (19th June 2020) - Panwar, Hemlata; Tandon, Ashwani; Joshi, Deepti; Goel, Garima; Mahabharti, Kodavali; Kapoor, Neelkamal
Abstract: Background: Fine‐needle aspiration cytology (FNAC) being a fast technique is used as a primary investigation to diagnose wide spectrum of hand, wrist, and foot lesions. These sites are prone to trauma, reparative, and infectious process, which forms mass lesions mimicking neoplasia. Our study highlighted the importance of FNAC with the chance of reduction in biopsy or excision. Aims and objectives: To report the prevalence and cytomorphological spectrum of hand and foot lesions with the aim of consolidating the diagnostic potential and also correlate the cytological evaluation with histopathology. Materials and methods: This retrospective observational study was done in central India for the period of 5.5 years. The archive cytology slides of patients with palpable lesions at these sites are reviewed and analyzed. Results: Of the total 6512 FNAC cases, 115 cases presented as swelling in the hand, wrist, and foot are reviewed. Age ranged from 4 months to 80 years with M:F = 1.25:1. Of the 111 satisfactory smears (96.7%), 21 cases (18.9%) diagnosed as inflammatory lesion, including synovitis, tuberculosis, gout, and fat necrosis. Sixty cases as benign non‐neoplastic (tumor‐like) lesions with the most common being ganglion (29). Of the 30 neoplastic lesions, 26 were benign tumor with the most common being mesenchymal neoplasms (19), followed by giant cell tumor of tendon sheath. Malignant tumors included malignant melanoma, small round cell tumor, and squamous‐cell carcinoma. Conclusion: FNAC is useful investigation for early diagnosis of hand and foot lesions. These lesions are benign mostly with less malignancy occurrence (<2%), compared with other soft tissue lesions.